BEHAVIOR OF BEARING CAPACITY ON PILE FOUNDATION DURING FLUCTUATING GROUNDWATER LEVEL - Intui, Sutasinee; Soralump, Suttisak; Inazumi, Shinya (GEOMATE Journal, 2022)
The recent decrease in the groundwater level in the Bangkok area has mainly occurred due to inappropriate water pumping for industrial and agricultural activities. This inappropriate pumping is not only causing land subsidence but is also affecting the load capacity of the soil around the piles. At present, the groundwater level in the Bangkok area is showing a tendency to increase to the ground surface thanks to the reduction in groundwater pumping. This is an important issue of research into the soil load capacity behavior around piles with changes in the groundwater level. This study focuses on the bearing capacity behavior of a single pile by comparing the results of centrifuge tests and the results of previous studies. The test results are compared for each groundwater level. Finally, the results of the tests are summarized into two parts. The first part is that the bearing capacity of the soil around the pile is related to the changing groundwater level but inversely. The soil strength is seen to decrease as the groundwater level increases or rises to the ground surface. The bearing capacity in clay mainly depends on the consolidation process. The second part is that the results of the pile load behavior from the centrifuge tests tend to be like those of the previous studies. Therefore, centrifuge test results can be used to evaluate and design pile foundations in the Bangkok area with changing groundwater levels.